Enamine Compounds - Deyoung, Gwyn, author 648433 (Delhi, India : Library Press, 2012)
An enamine is an unsaturated compound derived by the reaction of an aldehyde or ketone with a secondary amine followed by loss of H2O. The word "enamine" is derived from the affix en-, used as the suffix of alkene, and the root amine. This can be compared with enol, which is a functional group containing both alkene (en-) and alcohol (-01). If one of the nitrogen substituents is a hydrogen atom, H, it is the tautomeric form of an imine. This usually will rearrange to the imine; however, there are several exceptions (such as aniline). The enamine-imine tautomerism may be considered analogous to the keto-enol tautomerism. In both cases, a hydrogen atom switches its location between the heteroatom (oxygen or nitrogen) and the second carbon atom. Enamines are both good nucleophiles and good bases.